4F‐MDMB‐BINACA: A New Synthetic Cannabinoid Widely Implicated in Forensic Casework*†. Issue 5 (1st July 2019) - Krotulski, Alex J.; Mohr, Amanda L.A.; Kacinko, Sherri L.; Fogarty, Melissa F.; Shuda, Sarah A.; Diamond, Francis X.; Kinney, William A.; Menendez, M.J.; Logan, Barry K.
Abstract: This is the first report regarding the characterization of the new synthetic cannabinoid 4F‐MDMB‐BINACA. 4F‐MDMB‐BINACA was first analytically confirmed in seized drug material using gas chromatography–mass spectrometry (GC‐MS), liquid chromatography–quadrupole time‐of‐flight mass spectrometry (LC‐QTOF), and nuclear magnetic resonance (NMR) spectroscopy. Subsequent to this characterization, 4F‐MDMB‐BINACA was detected in biological specimens collected as part of forensically relevant casework, including medicolegal death investigations and drug impaired driving investigations, from a variety of regions in the United States. Further analysis of biological specimens resulted in the identification of the metabolites 4F‐MDMB‐BINACA 3, 3‐dimethylbutanoic acid and 4‐OH‐MDMB‐BINACA. 4F‐MDMB‐BINACA is appearing with increasing frequency as a contributory factor in deaths, creating morbidity and mortality risks for drug users. Laboratories must be aware of its presence and impact, incorporating 4F‐MDMB‐BINACA into workflows for detection and confirmation.